The role of the speech technique and culture of speech in the TV presenter skills (Herald of Journalism, 2018)
The article discusses the role of speech technology and culture speech with scientific and theoretical point of view specifies the target of their laws and principles in the framework of professional activities. Author, listing of definitions of scholars and orators of the art and culture of speech ,characterizes a qualitative indicator of the manner of speech on television.